Building, Encoding, and Annotating a Corpus of Parliamentary Debates in TEI XML: A Cross-Linguistic Account - Naomi Truan; Laurent Romary (Journal of the Text Encoding Initiative)
This paper introduces an integrative and comprehensive method for the linguistic annotation of parliamentary discourse. Initially conceived as documentation for a specific and small-scale research project, the annotation scheme takes into account national specificities and is geared to proposing an annotation scheme that is both highly standardized and adaptable to other research contexts. In this paper we present a specific application of the Text Encoding Initiative (TEI) framework applied to a subset of official transcripts of plenary proceedings in three parliamentary cultures. The TEI annotation scheme proposed here has two main applications: first, it serves as a basis for encoding parliamentary corpora by providing a systematic way of annotating both elements within the text (e.g., turns, incidents, and interruptions) and the metadata associated with it (e.g., variables pertaining to the speaker or the speech event); second, it provides a cross-linguistic empirical basis for further annotation projects.